Strategi Guru Geografi dalam Pembelajaran Penginderaan Jauh Kelas XII di SMA Al-Azhar 5 Cirebon - Ruhyati, Nur Aliyah; Banowati, Eva (Edu Geography, 2019)
The purpose of the study is to determine the teacher's strategy in planning learning, analyzing the teacher's strategy in the implementation of learning, and evaluating learning outcomes. The population is used as a research is of geography teachers 1 person and 27 students. The variable of this research is the variable X, namely the teacher's strategy in learning consists of planning, implementation, media, and methods. The variable Y that is Study result consist of affective, cognitive, and psychomotor. Data collection techniques include observation, tests, questionnaires, documentation, and interviews. Data analysis techniques used descriptive analysis of percentage and crosstab. The results of this study are the teacher compiling learning planning in the form of syllabus and RPP, the implementation of learning using contextual learning strategies. The media obtained an average of 59.4% and the method gained an average of 95%. The results of the parameters of remote sensing learning in the research location are very good 85% although not optimal. Student learning outcomes are used as an assessment in the form of affective, cognitive and psychomotor. Tujuan penelitian ini untuk mengetahui strategi guru dalam perencanaan pembelajaran, menganalisis strategi guru dalam pelaksanaan pembelajaran, dan mengevaluasi hasil belajar. Populasi penelitian yaitu guru geografi 1 orang dan 27 siswa. Variabel penelitian ini adalah variabel X yaitu strategi guru dalam pembelajaran terdiri dari perencanaan, pelaksanaan, media, dan metode. Variabel Y yaitu hasil belajar terdiri dari hasil belajar afektif, kognitif, dan psikomotorik. Teknik pengambilan data berupa observasi, tes, kusioner, dokumentasi, dan wawancara. Teknik analisis data menggunakan analisis deskriptif persentase dan crosstab. Hasil penelitian ini yaitu guru menyusun perencanaan pembelajaran berupa silabus dan RPP, pelaksanaan pembelajaran menggunakan strategi pembelajaran kontekstual. Media memperoleh rata-rata 59,4% dan metode memperoleh rata-rata 95%. Hasil dari parameter pembelajaran penginderaan jauh di lokasi penelitian sangat baik 85% walaupun belum optimal. Hasil belajar siswa yang dijadikan penilaian berupa hasil belajar afektif, kognitif dan psikomotorik.